Surgical occlusion of leaking bronchus by a serratus anterior flap in a child with langerhans cell histiocytosis - Lokavarapu Manoj Joshua; Ashok Rijhwani; Manish Kumar Gupta; Enono Yhoshu; Gyanendra Chaudhary (Wolters Kluwer Medknow Publications, 2021)
Langerhans cell histiocytosis is an uncommon disease of childhood. Intrathoracic transposition flaps have been described for a management of number of conditions. We discuss our experience of the use of serratus anterior flap for the obliteration of a pulmonary bulla with a communicating airway, in a 1½-year-old pediatric patient with multisystem Langerhans cell histiocytosis who presented with recurrent pneumothorax with empyema due to rupture of bullae.